Linking cultural dimensions and CSR communication emerging research and opportunities - Palazzo, Maria (Advances in business strategy and competitive advantage., 2019)
"This book proposes an extension of existing studies that explore the link between CSR and cultural dimensions and demonstrate that cultural dimensions and CSR communication are independent on corporate websites. It also offers guidelines to implement culturally congruent websites and to measure the degree of cultural adaptation"--